Design Factors in Evaluating and Formulating IT Governance Systems in Public Organizations - Muhammad Rifai Katili; Lanto Ningrayati Amali; Siiti Suhada (Ikatan Ahli Informatika Indonesia (IAII), 2023)
The application of information technology (IT) by central and regional governments to public services is intended to efficiently and effectively improve performance and public services. However, many studies have shown the ineffective application of IT. In Gorontalo province, this can be seen in the e-readiness value of Gorontalo province as a prerequisite for successful IT implementation, which is still at 58.15 points, which means that it is at a moderate level of readiness. This shows that implementing IT governance in the local government of Gorontalo province is still not optimal in terms of performance or public services. This study aims to identify the design factors that need to be considered when implementing IT Governance to achieve better public service performance. This study uses a quantitative approach based on a survey method. The results showed six models at Level 3: BAI06, BAI07, DSS01, DSS03, DSS04, and DSS05. In addition, four models were at level 4: APO12, APO13, BAI10, and DSS02. Levels 3 and 4 show that the IT governance capability of the Gorontalo provincial government in each model is not yet optimal. This study recommends that the Gorontalo provincial government evaluate and formulate an effective IT Governance system by focusing on each model's IT Governance design factors to improve public service performance.